An Ultra-Low-Power Black Phosphorus (B-Ph)/Si Heterojunction Dopingless-Tunnel FET (HD-TFET) with Enhanced Electrical Characteristics. (January 2021) - Misra, Rahul; Singh, Kunal; Kumar, Mirgender; Rastogi, Ravi; Kumar, Arun; Dubey, Sarvesh
Abstract: The execution of two-dimensional (2D) layered material in the source-region of a silicon-based tunnel field-effect transistors (TFETs) is proposed for ultra-low-power (ULP) applications. In the present simulation-based study, the layered black phosphorus (B-Ph) with moderate value of bandgap and low effective mass is used in the source-region of the SOI (silicon-on-insulator) heterojunction dopingless TFET (HD-TFET). The investigations of device characteristics are done against the channel lengths ranging from 45 nm to 14 nm. The device offers promising subthreshold characteristics for ULP applications with extremely low subthreshold swing of 1.77 mV/Decade, and I o n I o f f ratio of ≈ 10 9 . The analog and radio-frequency (RF) performances of the B-Ph/Si HD-TFET are observed promising for the possible implementation at circuit level. Moreover, the proposed device offers a high degree of linearity with the maximum compression point of − 20 dB . The numerical simulation of the proposed device is performed on ATLAS™, a two-dimensional (2D) device simulator from Silvaco. Highlights: A heterojunction tunnel FET is proposed in which a 2D material called black phosphorus is used as source-material for up to 14nm of channel length. The leakage current ( I o f f ) is 10 − 16 A / μm rendering I o n I o f f current ratio of the order of 10 9 with tremendously small subthreshold swing of 1.77 mV/Decade. The proposed B-Ph/Si HD-TFET demonstrates TGF (10 5 ) with gate capacitance ( C G G ) of 0.105 fF / μm . Cut-off frequency F t is in terahertz range ( 0.1 × 10 12 Hz) with very low EDP ( 0.5 fJ − ps / μm ). The device shows very high value of VIP2, VIP3 and IIP3. Maximum linearity with high value of 1-dB compression point of − 20 dB at 14 nm of channel length is achieved.